Fenomenologi Komunikasi Antarbudaya Anggota HIMMPAS - Sanjani, Galuh Amelia; Rochmaniah, Ainur (Jurnal Pustaka Komunikasi, 2023)
In everyday life, we always communicate with various kinds of people from various cultural, educational, economic and social backgrounds, this then makes us carry out intercultural communication. This also happened in one of the Student Activity Units (UKM) of Muhammadiyah University of Sidoarjo, namely HIMMPAS (Muhammadiyah Student Association of Sidoarjo Nature Lovers). This study aims to analyze the phenomenology of intercultural communication in the adaptation process of HIMMPAS members at Muhammadiyah University of Sidoarjo. The research method used in this research is qualitative with a phenomenological approach. The writing format is in the form of a case study by describing the subject's experiences with the epoch method. Data collection techniques in this study used observation, literacy studies, and interviews. Based on Uncertainty Reduction Theory, assumes that interaction is very important because the purpose of communication is to reduce uncertainty between strangers when meeting and having conversations. This study concludes that intercultural communication occurs among HIMMPAS members when members from Sidoarjo interact with members from outside Sidoarjo as well as between members from outside Sidoarjo and members who also come from outside Sidoarjo.